Estudo do potencial biotecnológico de Aniba canelilla (H.B.K) Mez para obtenção de cosméticos - Silva, Geverson Façanha da (2012)
The pressure of the exploitation over the main species of Lauraceae that produce essential oils has led to a drastic reduction of its natural properties. Given the increasing demand of the cosmetic, perfume and pharmaceutical industries, the market value of these oils has increased, thus boosting the predatory exploitation of these species. Therefore, this work aims to evaluate on Aniba canelilla some biological activities, its toxic potential and offer an alternative for the sustainable utilization of byproducts generated by the essential oils industry, in order to produce cosmetic formulations, taking advantage of the Amazon's natural resources which present biotechnological potential. The oil extraction was carried out in a Clevenger type apparatus. On the distillates (oil and hydrolate) and on ethanol extracts of leaves and branches of Aniba canelilla, were verified the antibiotic activity (antifungal and antibacterial) against the fungi Candida albicans (a human pathogen), Corynespora cassiicola (tomato pathogen), Didymella bryoniae (pathogen of watermelon), and the bacteria Pseudomonas aeruginosa (Gram negative) and Staphylococcus aureus (Gram-positive). The results were quantified by the size of the inhibition zone in relation to the control solution. It was also evaluated the antioxidant activity, according to the ability of the radical 2,2-diphenyl-1-picryl-hidrazila (DPPH·) scavenger by monitoring the decrease in the absorbance. The extracts were subjected to liquid-liquid partition and tested again in order to obtain a semi-purification of its compounds. The toxicity of hydrolate and its consequent environmental impact were also evaluated, through cytotoxic assays on Artemia salina by determining the LC50 and the monitoring of genotoxic and hematological parameters on Colossoma macropomum. Finally, it was evaluated the primary stability of a cosmetic formulated from hydrolate, essential oil and extracts of Aniba canelilla. The ethanolic extract from leaves and branches demonstrated an outstanding antioxidant potential, and after liquid-liquid partition, the hydroalcoholic phase showed to be even more promising. The essential oils showed no significant inhibition percentage of DPPH. The hydrolate showed inhibition of the radical, and has biotechnological potential for use in cosmetics. Moreover, essential oils were highly toxic against C. albicans and D. bryoniae being probably the responsible for this activity, the major compound 1-nitro-2-phenylethane. In evaluating the cytotoxicity of hydrolate on A. salina, it was verified its high toxicity, indicated by lower LC50 value ≈ 5% (v /v). Considering these data, to evaluate the physiological responses in C. macropomum was used a hydrolate concentration of 1%, which promoted genotoxic damage and changes in hemoglobin and hematocrit, indicating respiratory distress on fishes. Finally, it was designed a body moisturizer, which was subjected to preliminary stability tests, being approved in cooling and centrifugation test, but disapproved on tests of thermal stress and freeze-defrost cycles. Hence, it is necessary to elaborate a new formulation. With this work, it can be concluded that A. canelilla have a promising potential to be exploited by the biotech industry in the preparation of cosmetic anti-aging creams and antifungal formulations. Keywords: Antifungal, Antibacterial, Antioxidant, Toxicology, Phytocosmetics.